Big-Deal Serial Purchasing : Tracking the Damage. - Crawford, Walt (Library technology reports., 2014)
The "Big Deal" looked like a good deal, a true win-win. But while the Big Deal has lowered the rate of serial price inflation, for many libraries the pricing remains unsustainable